Erythrocyte Osmotic Fragility of Nera Black Fowls of Two - Age Groups - Azeez, O.I.; Oyewale, J.O.; Okunola, O.O. (International Journal of Poultry Science, 2009)
The erythrocyte osmotic fragility and other erythrocyte indices in fowls of two different age groups (7-9 week-old and 49 week-old) were studied using Nera Black strain usually raised commercially for egg production in Nigeria. Erythrocytes in the 49 week-old birds were more fragile than those in the 7-9 week-old at sodium chloride (NaCl) concentrations of 0.2% (p